Digitalisation as Discursive Construction: Entrepreneurial Labour and the Fading of Horizons of Expectations for Newcomer Journalists. (2nd January 2023) - Trimithiotis, Dimitris; Stavrou, Sophia
ABSTRACT: This article contributes to the literature on digitalisation of journalism by approaching the topic from an innovative angle, as a subjective, contextual, and dynamic process. The study focuses on digitalisation as a discursive construction and, particularly, on entrepreneurial journalism as an essential element of this construction. This allows to understand how it is interpreted and appropriated by actors of the journalistic field in their practices, as well as the impact of digitalisation on employment and the work futures of newcomer journalists in the current labour market. The study is based on interviews with journalism graduates and with media administrators in Cyprus, enhanced by quantitative data on recent graduates' employment and relation to work. The findings show how discourses forge the ideal type of the digital journalist, which encompasses the digital skills and the subjective attributes of a performant digital personality. Within the current organisation of the labour market, this re-skilling of journalistic activities can lead to a dis-qualification of journalism work positions occupied by newcomer journalists. As such, digitalisation affects the relation to work of graduates, particularly their horizons of expectations, which are fading, especially for some of them, confined in presentism, engaging in entrepreneurial strategies within a waged relation.